Animated film and disability : cripping spectatorship - Greenberg, Slava (Indiana University Press, 2022)
"While many films portray disability as a spectacle, the cinematic field of "crip animation" (a term that purposefully makes readers uncomfortable) has the power to challenge the ableist gaze and immerse viewers in an alternative bodily experience. Animated Film and Disability analyzes over 30 animated works that represent disabled characters, including Finding Nemo, Inside Out, and BoJack Horseman, and contends that crip animation has the power to disorient viewers and force them to become aware of their own bodies. Slava Greenberg focuses not only on representations of internal psychological worlds and conditions but also the subjective viewpoints of people with disabilities. In addition, Greenberg explores physical and sensory accessibility in theaters and suggests new ways to accommodate cinematic screenings for disabled audiences. Offering an introduction to disability studies and crip theory for film, media, and animation scholars, Animated Film and Disability demonstrates that crip animation has the power to breach the spectator's comfort, subvert tradition, and create deeper understanding"--